2006
DOI: 10.1017/s0022215106000697
|View full text |Cite
|
Sign up to set email alerts
|

Myringoplasty

Abstract: There is marked diversity in the reported success rates for achieving an intact tympanic membrane following myringoplasty. Controversy exists about the factors thought to influence surgical outcome. Both of these facts have important implications for obtaining informed consent prior to surgery. This study reviews the factors thought to determine the likelihood of achieving complete closure of the tympanic membrane following surgical closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 21 publications
2
82
1
Order By: Relevance
“…[5,6] with use of overlay technique, anterior blunting, graft lateralization, thickening of the drum, iatrogenic cholesteatoma or post-inflammatory ear canal stenosis was not observed. The good results of overlay technique is attributed to the post-auricular approach.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[5,6] with use of overlay technique, anterior blunting, graft lateralization, thickening of the drum, iatrogenic cholesteatoma or post-inflammatory ear canal stenosis was not observed. The good results of overlay technique is attributed to the post-auricular approach.…”
Section: Discussionmentioning
confidence: 94%
“…In the year 1960, Shea and Tabb. [5][6][7] introduced the concept of placing the graft material medial to the remnants of the drum. Underlay myringoplasty is widely used and relatively simple to perform.…”
Section: Introductionmentioning
confidence: 99%
“…26 Aggarwal et al in their study observed higher success rates with smaller perforations (less than 50% of pars tensa). 27 Yoon et al in their study concluded that there were no significant relationships between surgical success rate and the status of the contralateral ear. 28 But Merendra et al reported that multivariate analysis demonstrated that disease of the contralateral ear and a large tympanometric volume were statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…5 Because of these reasons it is not possible to guarantee 100% success rate to any patient, though the surgical procedure has excellent success rate.…”
Section: Discussionmentioning
confidence: 99%